Problems and prospects of bovine tuberculosis serological diagnosis - M. O. Baratov (Ветеринария сегодня)
For the purposes of tuberculosis eradication on any tuberculosis-infected farm, it is necessary to identify tuberculin anergic animals, being a potential source of the infection. The purpose of this study was to analyze the role of complement fixing and haemagglutinating antibodies for the detection cattle infected with bovine tuberculosis (TB). 977 cattle of different sex and age groups on two tuberculosis-infected farms were tested thrice over time. After 35 days all tuberculin reactive cattle (132 animals; 13.5%) were subjected to complex testing using allergy and serology methods. After 40 days, (Stage 3) animals demonstrating apparent specific antibody activity and low cell immunity were tested. Allergy tests were proved to be non-informative to diagnose tuberculosis on infected farms. Complement fixing and haemagglutinating antibodies were found to be active in tuberculin anergic animals. A higher antigenicity of Ukrainian RIEVM TB antigen complex as compared to Siberian RVI one was revealed by complement fixation test as well as by indirect haemagglutination test using VIEV polysaccharide antigen; the detection rate was 68 (7.0%), 28 (2.9%) and 299 (30.6%) respectively. The correlation between seropositivity and immunoreactivity was not established. Animals, positive in complement fixation and indirect haemagglutination tests, did not react to tuberculin. Nineteen out of twenty tuberculin reactive animals showed post mortem lesions, consistent with their seropositivity during post-mortem inspection; moreover, the postmortem lesions of animals, positive in complement fixation test using Siberian RVI antigen, were consistent in all cases. The results obtained suggest a high performance of allergy test and serological test combination and a promising potential of their complex use for tuberculosis diagnosis in cattle.